Implementation of Educational Scholarship Programs at Amil Zakat Institutions in West Kalimantan: An Evaluation Study of the CIPP Model - Wardi, Suhra; Sumin, Sumin (QALAMUNA: Jurnal Pendidikan, Sosial, dan Agama, 2022)
Program evaluation is needed to improve the quality of education funding through scholarships for underprivileged students so they can continue quality education. This study aims to evaluate the implementation of educational funding through a scholarship program organized by the Amil Zakat Institute of the Great Mosque of Mujahiddin, West Kalimantan, by using the CIPP model, which consists of context, input, process, and product elements. Program evaluation is carried out through stages, interviews, observation, and documentation. The results obtained are a score of 92.86 and have the "very good" category. However, several improvements need to be made by educational units to improve quality in implementing inclusive education in mathematics learning. The improvements are the addition of special tutors (GPK) who can specifically handle students with a variety of special needs and the procurement of data provision regarding the continuity of inclusive education programs for learning mathematics at the next level and level. Thus, the CIPP evaluation model can be used to evaluate inclusive education programs in mathematics learning in junior high schools, which provide outputs in the form of final scores, categories, and recommendations for improvement.